MODEL PEMBUKUAN SEDERHANA UKM BAKSO KLASTER SEMI MODERN DI WILAYAH KOTA SEMARANG - C Tri Widiastuti; Aprih Santoso; Anandha Anandha (STIE Pelita Nusantara Semarang, 2018)
Financial bookkeeping will result in a more informative financial report in order to provide complete information to third parties. But in practice the owner of SMEs are unable to provide financial information in the absence of financial statements. Low quality of human resources and lack of understanding of financial statements are the reason why SMEs owners do not make financial reports. This study aims to analyze financial bookkeeping that has been done and designed a simple financial bookkeeping model for the owner of SMEs semi-modern cluster bakso in the city of Semarang. The research method used is qualitative with data collection techniques through in-depth interviews conducted on key informants. Informants in this study are the owner of SMEs bakso in the city of Semarang. Data analysis techniques using Miles and Hubermans model with stages include: data reduction, data presentation and conclusion drawing/verification. While the data validity test using credibility test through extension of observation and trianggulasi.